Population Growth and Long-Distance Vagrancy Leads to Colonization of Europe by Elegant Terns Thalasseus elegans - Veit, Richard Reed; Velarde, Enriqueta; Horn, Michael H.; Manne, Lisa L. (Frontiers in Ecology and Evolution, 2021)
Elegant terns Thalasseus elegans breed in a very limited area of the northern Gulf of California and the Pacific coast of southern California, with up to 95% (mean 78%, 1991–2014, Perez et al., 2020) of the population nesting on Isla Rasa in the northern Gulf of California. On Isla Rasa, the primary nesting colony, elegant terns suffered predation by rodents which raised the possibility of population extinction, with a substantial proportion of the world population nesting on this single island. Because of this threat, rodents were successfully removed from Isla Rasa in 1995. The removal of rodents from Isla Rasa led to a near immediate increase in the population of elegant terns. That increase was associated with a changing pattern in dispersal by the terns, including extraordinary movements to the Gulf of Mexico, the Atlantic coast of the United States north to Massachusetts, and, remarkably, to western Europe. A few elegant terns successfully bred at these European localities during 2009 to the present. In this paper we use this exceptional example of long-distance dispersal to illustrate how rapid population growth during ∼ 1995 to present can lead to successful colonization of remote sites through repeated instances of vagrancy. We tested four Hypotheses that together support the idea that the growing population of elegant terns has produced increasing numbers of young, and these young have spread, through the mechanism of vagrancy, to the Pacific Northwest, the east coast of the United States, and western Europe. Our Hypotheses are: (1) The nesting population of elegant terns within their core nesting range has increased since removal of rodents from Isla Rasa; (2) Occurrence of vagrant elegant terns in the Pacific Northwest is driven by population growth within the core breeding range. (3) Occurrence of vagrant elegant terns at the east coast of the United States is driven by population growth within the core breeding range. (4) Occurrence and colonization of western Europe by elegant terns is driven by nesting population size within the core breeding range. Corollaries of these Hypotheses are, (i) that there is a time lag in occurrence of vagrants at each of these areas, based on increasing distance from the core breeding range and (ii) the number of vagrants in any given year is also related to sea surface temperature (SST), as expressed by Oceanic Niño Index, a proxy for food resource levels. Generally we found strong statistical support for each of these Hypotheses; an exception was for the occurrence of elegant terns in the Pacific Northwest, which initially occurred following El Niño events (low food supply) and profound breeding failure, but later corresponding to cold water years with high breeding success. We use elegant terns, exceptional for the highly restricted breeding range and sustained population growth over 25 years, to illustrate how growing populations may colonize very distant habitats through repeated instances of vagrancy.